THE ANALYSIS OF GRAMATICAL AND LEXICAL ERRORS ON THE STUDENTS' THESES OF IAIN TAKENGON - Shaumiwaty, Shaumiwaty; Munandar, Imam (Jurnal As-Salam, 2022)
This research used the Error Analysis (EA) method to examine the grammatical mistakes made by English department students of the State Institute of Islamic Studies (IAIN) Takengon. The thesis works produced by those students were the focus of this study. Six students' theses were mined for information, specifically chapters four and five. The authors collected data from students, recognized grammatical faults, categorized errors in students' theses to estimate the frequency of errors, and then converted the data into percentages for analysis. Evidence suggests eleven distinct categories of writing mistakes made by students. There are 6% cases of improper subject-verb agreement, 3% cases of wrong word order, 10% cases of improper preposition, 17% cases of improper article use, 3% cases of improper pluralization, 16% cases of improper punctuation, 6% cases of improper auxiliary use, 24% cases of obscene, unnecessary words, 6% cases of wrong word choice, 6% cases of improper parallel structure, and 3% cases of redundant expression. In addition, the author counted 175 different typos. Punctuation, introductory phrase, and adverbial errors predominate. According to the findings, students' grammatical mistakes are fueled by their inability to master the rules of the target language and their limited familiarity with its vocabulary and structures.